2021
DOI: 10.1177/24727512211023340
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a Combined Frontal Bone and Orbital Roof Defect With Associated Meningoencephalocele Using 3D Modeling and 3D Navigation

Abstract: Introduction: Orbital roof fractures are uncommon and normally associated with high energy trauma in which multiple other injuries are present. Most can be managed non-operatively with close observation. However, in a small proportion the defect is such that it permits the development of a meningoencephalocele, which can cause exophthalmos, a reduction in visual acuity and pain, all of which are unlikely to improve without surgical treatment. In light of their scarcity and the potential of serious risks with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“… 7 , 8 , 9 , 10 , 16 In a recent review of orbital roof fractures complicated by meningoencephaloceles, 9 out of 20 reported cases since the year 2000 had MVC as the mechanism of injury. 11 Including our patient, there have been five reported cases since 1970 of GSW injuries resulting in traumatic orbital encephalocele. An association between mechanism of injury and the likelihood of developing a traumatic orbital encephalocele secondary to orbital roof fractures may exist, however, further investigation is needed.…”
Section: Discussionmentioning
confidence: 92%
“… 7 , 8 , 9 , 10 , 16 In a recent review of orbital roof fractures complicated by meningoencephaloceles, 9 out of 20 reported cases since the year 2000 had MVC as the mechanism of injury. 11 Including our patient, there have been five reported cases since 1970 of GSW injuries resulting in traumatic orbital encephalocele. An association between mechanism of injury and the likelihood of developing a traumatic orbital encephalocele secondary to orbital roof fractures may exist, however, further investigation is needed.…”
Section: Discussionmentioning
confidence: 92%